2008
DOI: 10.1097/bot.0b013e318160c84c
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical Comparison of the Locking Compression Plate (LCP) and the Low Contact-Dynamic Compression Plate (DCP) in an Osteoporotic Bone Model

Abstract: In a synthetic model, the LCP was mechanically superior to the DCP when used as a bridging plate and tested in axial compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 22 publications
4
59
0
Order By: Relevance
“…Union was achieved in 16/18 segments in a mean time of 12 weeks [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Union was achieved in 16/18 segments in a mean time of 12 weeks [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of locking plates include increased stability [1,12], as well as minimal soft tissue damage due to their insertion in the submuscular-extraperiosteal plane and the percutaneous insertion of both the plates and the screws. Although the stability obtained with traditional compression plates is probably adequate for pediatric patients, the reduction of the soft tissue dissection is a significant advantage and may promote earlier rehabilitation, especially in neuromuscular patients.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Analogous biomechanical properties of LCPs and DCPs have been delineated in a radius cadaver model by Gardner et al 21 However, Snow et al, in a biomechanical study of an osteoporotic bone model discovered the LCPs to perform better in the axial compression test when used as a bridge plate against the conventional plates. 22 Furthermore, Doornink et al validated that hybrid plates impart higher torsional strength, similar bending strength, and a minimal decrease in axial strength than all locked plates in a biomechanical study of an osteoporotic diaphyseal fracture model. 23 In spite of these experimental studies confirming the lead of LCPs over DCPs and all locked plates, clinical trials have failed to reestablish this in forearm fractures.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a biomechanical study of an osteoporotic bone model, Snow et al [25] found the LCP, which was used as a bridge plate, more successful in the , 2017. Experimental studies have reported that LCPs are superior to DCPs and all locked plates in osteoporotic fracture models.…”
Section: Imad World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…Experimental studies have reported that LCPs are superior to DCPs and all locked plates in osteoporotic fracture models. [25,26] However, clinical trials have failed to demonstrate the superiority of LCPs over conventional plates in forearm fractures. [10,11] The series reported by…”
Section: Imad World Journal Of Pharmaceutical Researchmentioning
confidence: 99%